Timing and pace of dairying inception and animal husbandry practices across Holocene North Africa - Dunne, J.; di Lernia, S.; Chłodnicki, M.; Kherbouche, F.; Evershed, R.P. (Quaternary international, 2018)
The timing and extent of the adoption and exploitation of domesticates and their secondary products, across Holocene North Africa, has long been the subject of debate. The three distinct areas within the region, Mediterranean north Africa, the Nile Valley and the Sahara, each with extremely diverse environments and ecologies, demonstrate differing trajectories to pastoralism. Here, we address this question using a combination of faunal evidence and organic residue analyses of c. 300 archaeological vessels from sites in Algeria, Libya and Sudan. This synthesis of new and published data provides a broad regional and chronological perspective on the scale and intensity of domestic animal exploitation and the inception of dairying practices in Holocene North Africa. Following the introduction of domesticated animals into the region our results confirm a hiatus of around one thousand years before the adoption of a full pastoral economy, which appears first in the Libyan Sahara, at c. 5200 BCE, subsequently appearing at c. 4600 BCE in the Nile Valley and at 4400–3900 BCE in Mediterranean north Africa.